51Cr-EDTA plasma clearance in children: One, two, or multiple samples?. Issue 3 (21st January 2022) - Pottel, Hans; Goffin, Karolien; De Waele, Liesbeth; Levtchenko, Elena; Delanaye, Pierre
Abstract : Abstract: Plasma disappearance curves using multiple blood samples are a recognized reference method for measuring glomerular filtration rate (GFR). However, there is no consensus on the protocol for this type of measurement. A two-compartment model is generally considered acceptable for the mathematical description of the concentration–time decay curve. The impact of the fitting procedure on the reported GFR has not been questioned. We defined 8 different fitting procedures to calculate the area under the curve, and from this area under the curve, the GFR. We applied the 8 fitting methods (all considering a full concentration–time curve) on the multiple sample data (8 samples) of 20 children diagnosed with Duchenne muscular dystrophy. We evaluated the effect (variability) on the reported GFR from the different fitting methods and compared these results with GFR-values calculated from late samples only (samples after 120 minutes) and from one-sample methods. In 6 out of 20 cases, the fitting methods on the full concentration–time curve resulted in very different reported GFR-values, mainly because some methods were not able to fit the data, or methods resulted in GFR-values ranging from 0 to 120 mL/min. The reported GFR-result therefore strongly depends on the fitting method, making the full concentration–time method less robust than expected. Compared with a consensus reference GFR, the late sample models did not show fitting issues and may therefore be considered as more robust. Also the one-sample methods showed acceptable accuracy. The late sample methods (using 3 time-points) provide robust and reliable methods to determine GFR. Abstract : Supplemental Digital Content is available in the text